Quantitative proteomics of hamster lung tissues infected with SARS‐CoV‐2 reveal host factors having implication in the disease pathogenesis and severity. Issue 7 (9th June 2021) - Suresh, Voddu; Mohanty, Varshasnata; Avula, Kiran; Ghosh, Arup; Singh, Bharati; Reddy, Rajendra Kumar; Parida, Deepti; Suryawanshi, Amol Ratnakar; Raghav, Sunil Kumar; Chattopadhyay, Soma; Prasad, Punit; Swain, Rajeeb Kumar; et al.
Abstract: Syrian golden hamsters ( Mesocricetus auratus ) infected by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) manifests lung pathology. In this study, efforts were made to check the infectivity of a local SARS‐CoV‐2 isolate in a self‐limiting and non‐lethal hamster model and evaluate the differential expression of lung proteins during acute infection and convalescence. The findings of this study confirm the infectivity of this isolate in vivo. Analysis of clinical parameters and tissue samples show the pathophysiological manifestation of SARS‐CoV‐2 infection similar to that reported earlier in COVID‐19 patients and hamsters infected with other isolates. However, diffuse alveolar damage (DAD), a common histopathological feature of human COVID‐19 was only occasionally noticed. The lung‐associated pathological changes were very prominent on the 4th day post‐infection (dpi), mostly resolved by 14 dpi. Here, we carried out the quantitative proteomic analysis of the lung tissues from SARS‐CoV‐2‐infected hamsters on day 4 and day 14 post‐infection. This resulted in the identification of 1585 proteins of which 68 proteins were significantly altered between both the infected groups. Pathway analysis revealed complement and coagulation cascade, platelet activation, ferroptosis, and focal adhesion as the top enriched pathways. In addition, we also identified altered expression of two pulmonary surfactant‐associated proteins (Sftpd and Sftpb), known for their protective role in lung function. Together, these findings will aid in understanding the mechanism(s) involved in SARS‐CoV‐2 pathogenesis and progression of the disease.